Theory and practice of natural computing : 8th International Conference, TPNC 2019, Kingston, ON, Canada, December 9-11, 2019, Proceedings /: 8th International Conference, TPNC 2019, Kingston, ON, Canada, December 9-11, 2019, Proceedings. (2019) - Unknown
No abstract available